(untitled) (PRÁXIS EM SAÚDE, 2025)
The teaching project “PET in Schools,” linked to the Indigenous Tutorial Education Program (PETI), develops psychoeducational activities in a public school in the countryside of Rio Grande do Sul, with the aim of promoting the recognition and appreciation of Indigenous cultures. The initiative arose from the need to deconstruct stereotypes and broaden the understanding of the diversity of Indigenous peoples, based on Law No. 11.645/2008, which makes the teaching of Indigenous history and culture mandatory in schools. The activities took place monthly between March and December 2024, with 3rd to 5th grade elementary school classes. Workshops were held with traditional games, such as the maracá race and tug-of-war, as well as body painting with Indigenous motifs and discussion circles, always adapted to the children’s age group. The results revealed strong student engagement and interest in the topics addressed. Although some stereotyped representations still emerged, the project also sparked important reflections on Indigenous ways of life. The presence of Indigenous university students contributed to expanding the children’s perception of the plurality of these identities. It is concluded that experiences such as this foster education for diversity and should be permanently integrated into everyday school life.